Dietary Betaine Mitigates Hepatic Steatosis and Inflammation Induced by a High-Fat-Diet by Modulating the Sirt1/Srebp-1/Pparɑ Pathway in Juvenile Black Seabream (Acanthopagrus schlegelii) - Jin, Min; Shen, Yuedong; Pan, Tingting; Zhu, Tingting; Li, Xuejiao; Xu, Fangmin; Betancor, Mónica B.; Jiao, Lefei; Tocher, Douglas R.; Zhou, Qicun (Frontiers in Immunology, 2021)
The present study aimed to elucidate the mechanism of dietary betaine, as a lipid-lowering substance, on the regulation of lipid metabolism and inflammation in juvenile black seabream (Acanthopagrus schlegelii) fed a high fat diet. An 8-week feeding trial was conducted in black seabream with an initial weight of 8.39 ± 0.01g fed four isonitrogenous diets including Control, medium-fat diet (11 %); HFD, high-fat diet (17 %); and HFD supplemented with two levels (10 and 20 g/kg) of betaine, HFD+B1 and HFD+B2, respectively. SGR and FE in fish fed HFD+B2 were significantly higher than in fish fed HFD. Liver histology revealed that vacuolar fat droplets were smaller and fewer in bream fed HFD supplemented with betaine compared to fish fed HFD. Betaine promoted the mRNA and protein expression levels of silent information regulator 1 (Sirt1), up-regulated mRNA expression and protein content of lipid peroxisome proliferator-activated receptor alpha (pparα), and down-regulated mRNA expression and protein content of sterol regulatory element-binding protein-1(srebp-1). Furthermore, the mRNA expression levels of anti-inflammatory cytokines in liver and intestine were up-regulated, while nuclear factor kB (nf-kb) and pro-inflammatory cytokines were down-regulated by dietary betaine supplementation. Likewise, in fish that received lipopolysaccharide (LPS) to stimulate inflammatory responses, the expression levels of mRNAs of anti-inflammatory cytokines in liver, intestine and kidney were up-regulated in fish fed HFD supplemented with betaine compared with fish fed HFD, while nf-kb and pro-inflammatory cytokines were down-regulated. This is the first report to suggest that dietary betaine could be an effective feed additive to alleviate hepatic steatosis and attenuate inflammatory responses in black seabream fed a high fat diet by modulating the Sirt1/Srebp-1/Pparɑ pathway.